Ilex paraguriensis A. St Hil.: efeitos na prevenção das alterações cutâneas induzidas por radiação UVB - Cuelho, Camila Helena Ferreira (2016)
Daily basis, we are exposed to many environmental factors such as ultraviolet radiation and pollution, which are sources of free radicals. Although it‟s the most responsible for the biological effects related to skin cancer and photoagind, UVB radiation is only 10% of the total UV radiation can reach the Earth‟s surface. As a preventive measure, photo chemoprotectives, are oral or topical products incorporated plant extracts or isolated natural substances with antioxidant activity, inhibitors of MMPs and/or anti-inflamatory. Ilex paraguariensis A. St. Hil, known as yerba mate, is a native plant to South America. Previous studies showed high levels of bioactive cosmetic interest, such as: phenolic acids, flavonoids ant triterpenoid saponins. The main of the study was to investigate the potential photoprotective the crude extract of the leaves of Ilex paraguariensis in vitro e in vivo. The EXB was characterized by the dosages of the polyphenols, flavonoids and tannins by spectrophotometric methods; identifying and quantifying the chlorogenic acid and caffeic by LC/MS and HPLC; besides its antioxidant activity by in vitro methods. Cytotoxicity/Photostability and inhibitory activity of MMP-2 and -9 in different concentrations, were analyzed in vitro by measurement of cell viability in fibroblast culture (HFF-1 cells) and substrate zymography, respectively. The photoprotective effect of cream topic treatment containing EXB was evaluated in vivo by measuring the metalloproteinase activity, myeloperoxidase and collagen degradation, using heterogenic mice exposed to UVB (0,23 J/cm2). The flavonoid contents, polyphenols and tannins were 200 mg EQ/g; 265,4 mg EAG/g e 158,7 g EC/g. Through the HPLC, the chlorogenic acid content was quantified (19.26 mg/g) and caffeic acid (4.27 mg/g). The antioxidant potential was analyzed by the methods DPPH (IC50 39,73 μg/mL) and β-carotene (50,48% inhibition). In in vitro tests the EXB showed no cytotoxicity in HFF-1 cells. The EXB (50 μg/mL) non-irradiated UVB (0,23 J/cm2) proliferated HFF-1 cells, suggesting a possible photo instability the EXB. At the concentration of 100 μg/mL, reduced in vitro, 79,31% of pro-MMP-9 activity in a dose dependent manner. In vivo tests showed EXB formulation photoprotective efficacy by inhibiting the activity of MMP-2 (73,08%), pro-MMP-2 (67,71%) and pro-MMP-9 (89,86%), decreasing myeloperoxidase activity (71,1%) and preserving collagen an acute exposure to UVB radiation. The formulation containing the extract was shown to have a potential effect photoprotective and anti-aging.